2016
DOI: 10.1513/annalsats.201605-418oc
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Quality of Spirometry in Primary Care Offices

Abstract: Most spirometers tested were not accurate. The magnitude of the errors resulted in significant changes in the categorization of patients with obstruction. Acceptable-quality tests were produced for only 60% of patients. Our results raise concerns regarding the utility of spirometry obtained in primary care offices without greater attention to quality assurance and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…Thus, early detection of emphysematous changes would significantly assist in the timely head start of the currently available treatments such as corticosteroids, bronchodilators or the proposed autophagy augmentation strategy. Although, recent advances in emphysema detection methods and research aimed towards developing novel biomarkers has improved the possibility of early emphysema detection and therapeutic intervention, these techniques still lack the required accuracy and high-throughput screening capabilities [14]. Thus, clinical prognosis of COPD-emphysema still heavily relies on pulmonary function testing using spirometry [15], and no laboratory based precise diagnostic test exists for the early detection of COPD-emphysema initiation, especially in subjects who are smokers without any noticeable signs of lung function decline [16], such as shortness of breath (or dyspnea).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, early detection of emphysematous changes would significantly assist in the timely head start of the currently available treatments such as corticosteroids, bronchodilators or the proposed autophagy augmentation strategy. Although, recent advances in emphysema detection methods and research aimed towards developing novel biomarkers has improved the possibility of early emphysema detection and therapeutic intervention, these techniques still lack the required accuracy and high-throughput screening capabilities [14]. Thus, clinical prognosis of COPD-emphysema still heavily relies on pulmonary function testing using spirometry [15], and no laboratory based precise diagnostic test exists for the early detection of COPD-emphysema initiation, especially in subjects who are smokers without any noticeable signs of lung function decline [16], such as shortness of breath (or dyspnea).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, clinical prognosis of COPD-emphysema still heavily relies on pulmonary function testing using spirometry [15], and no laboratory based precise diagnostic test exists for the early detection of COPD-emphysema initiation, especially in subjects who are smokers without any noticeable signs of lung function decline [16], such as shortness of breath (or dyspnea). Although PFT/spirometry are quite robust in detection of airflow obstruction, they lack the sensitivity to quantify minimal early changes in pulmonary function [14]. Moreover, PFT procedure needs complete patient support that is sometimes unachievable especially in a sick subject.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall error rate (ie, poor quality blows) of 51.4% is comparable or lower than can be found in other studies, 12,25 one of which also identified that poor quality spirometry was higher among men compared with women. 20 There are studies which have previously identified shortfalls in the quality of primary care spirometry 26 ; hence, in that sense, our study could be said to be reflecting the real world of general practice. Originally, our study set out to recruit 600 participants and recruited 681 in total.…”
Section: Association For Respiratory Technology and Physiology Spirommentioning
confidence: 88%
“…25,26 In many specialized research centers, it is feasible to conduct high-quality spirometry in children as young as 3 years. 27,28 Translation of spirometry from a specialized test conducted in pulmonary function laboratories to the primary care setting has had mixed results, 29,30 especially for children for whom extra patience and a friendly environment are necessary to obtain reliable measurements. Early deficits in lung function may already be present by the time objective measurements of lung function are feasible to obtain, which represents yet another challenge.…”
Section: Spirometry: Population Vs Individual Measuresmentioning
confidence: 99%